DEVELOPMENT OF IN VITRO RELEASE TEST FOR CAPSAICIN TOPICAL GEL FORMULATIONS BY USING FRANZ DIFFUSION CELL - PRAKASH B. MODI, (International Journal of Pharma and Bio Sciences, 2014)
In vitro release test (IVRT) was developed for evaluation of release profile of Capsaicin from Capsaicin topical gel formulations. The method was developed using a Vertical Franz diffusion cell, commercially available synthetic membranes, Hydro alcoholic receptor medium and quantification by HPLC with UV detection. Good release profile of Capsaicin was observed with 0.2µm Teflon membrane, Ethanol: Water (70:30, %v/v) as receptor medium, 32°C as compartment temperature and 8 hrs study time. The aliquots of the samples at different time intervals were analyzed by HPLC with UV detection at 280 nm. Cumulative release and flux value of Capsaicin at the end of the study were found about > 15 µg/cm2 and 2.0 µg/cm2/hr respectively. Linearity was established for Capsaicin in the concentration range of 0.25-6.25 µg/ml with correlation co-efficient of 0.9998. Method showed discriminative power and sensitivity in the terms of quantification at lower concentration. Method can be utilized in pharmaceutical and Cosmetic industries for monitoring of batch to batch uniformity with respect to change in process and formulation composition and for comparative IVRT study of Generic formulations to built confidence prior to Clinical study.